A JAFROC study of nodule detection performance in CT images of a thorax acquired during PET/CT. Issue 3 (August 2017) - Thompson, J.D.; Wareing, A.; Szczepura, K.R.; Vinjamuri, S.; Hogg, P.
Abstract: Purpose: Two types of CT images (modalities) are acquired in PET/CT: for attenuation correction (AC) and diagnosis. The purpose of the study was to compare nodule detection and localization performance between these two modalities. Methods: CT images, using both modalities, of an anthropomorphic chest phantom containing zero or more simulated spherical nodules of 5, 8, 10 and 12 mm diameters and contrasts −800,  −630 and 100 HU were acquired. An observer performance study using nine observers interpreting 45 normal (zero nodules) images and 47 abnormal images (1–3 nodules; average 1.26) was conducted using the free-response receiver operating characteristic (FROC) paradigm. Data were analysed using an R software package implemented jackknife alternative FROC (JAFROC) analysis. Both empirical areas under the equally weighted AFROC curve (wAFROC) and under the highest rating inferred ROC (HR-ROC) curve were used as figures of merit (FOM). To control the probability of Type I error test alpha was set at 0.05. Results: Nodule detection as measured by either FOM was significantly better on the diagnostic quality images (2nd modality), irrespective of the method of analysis, [reader averaged inter-modality wAFROC FOM difference = −0.07 (−0.11, −0.04); reader averaged inter-modality HR-ROC FOM difference = −0.05 (−0.09,  −0.01)]. Conclusion: Nodule detection was statistically worse on images acquired for AC; suggesting that images acquired for AC should not be used to evaluate pulmonary pathology. Highlights: An evaluation of lesion detection performance in CT images of different qualities is proposed. JAFROC analysis showed that images acquired for attenuation correction are statistically poorer for lesion detection. This study suggests that images acquired for attenuation correction should not be used to evaluate pulmonary pathology.